Pengaruh Financial Stability dan External Pressure Terhadap Financial Statement Fraud - Elen Novita (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: The aims of this research are to obtain emprical evidence about the imfluence of financial stability and external pressure on financial statement fraud. Method: The method in this study used a purposive sampling method and obtained 17 companies with processed data of 85 annual financial reports. The sampling technique used is using purposive sampling technique. The data analysis method used is multiple linear regression analysis using SPSS version 20. Finding: The results of the study show that financial stability and external pressure have a significant effect on financial statement fraud partially and simultaneously. Novelty: The difference between this study and previous research lies in the way it is measured, namely financial stability is measured using the ratio of changes in assets per year (ACHANGE) and external pressure is measured using the leverage ratio (LEV).